Nachalo - Panfilov, Gleb (Soviet Union : Lenfilm, 1970)
A story of a young factory girl, Pasha Stroganova (Inna Churikova), who lives in provincial town and believes in her talent. From an amateur theater she is invited to play Jeanne D'Ark in a film, meanwhile her own life makes her face hard challenges.
Keywords: Fiction films